When Doctors Kill Who, Why, and How - Perper, Joshua A.; Cina, Stephen J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Some readers may be shocked by the title of this book, and some may wonder if it is necessary to raise the uncomfortable issue of killing by doctors. Killing is clearly antithetical to the Art and Science of Medicine, which is geared toward easing pain and saving lives rather than smothering them. Nevertheless, doctors are people too. Physicians have the same genetic library of enabling qualities and defects as the rest of us, but their vocation places them in a position where both good practice and bad practice can be exercised. The book begins by presenting the background against which medicine came into being and the forces that molded the social, psychological and professional profile of healers. It continues with profiles of infamous serial killer physicians throughout the world; some "practiced" over a hundred years ago, others in recent decades. There is a discussion of mass murdering physicians who chose dictatorship or terrorism over healing. Not-so-mad, but highly sadistic physician/ scientists will also be under their microscope. There is a discussion of high-profile cases, and the authors raise the specter of the first genetic homicide - murder by means of chromosomal manipulation. They also the authors also share their thoughts on some of the ethical issues facing physicians today and examine the gray areas between Medicine and Law. The book concludes with a look at current fashions and trends in medicine. Complementary medicine and alternative therapies may have brought relief to many patients, but they have also resulted in disability, suffering, and death. Through the review of a few high profile, drug-related fatalities, the celebrity-physician relationship will be explored. Finally, the authors examine how the doctor is portrayed in fiction and why medical professionals are featured so prominently on television. Dr. Perper and Dr. Cina have a combined medical experience spanning 60 years. As forensic pathologists, they witness death daily and have investigated hundreds of murders. They accept that most doctors are a force for good, but their book contains accounts of horrible atrocities and features descriptions of graphic murders committed by healers. By shining a cold light on the risks patients face today given the wide array of treatment options, the authors aim to accurately relay the circumstances of when, how, and why doctors kill.
Ethics and the Physician -- In the Beginning -- Perfect Intentions, Imperfect People -- When Doctors Kill -- The Alpha Killers: Three Prolific Murderous Doctors -- America$1 (Bs Contribution to Medical Mayhem -- International Men of Mystery: Other Medical Murderers -- To Catch a Killer: Investigating Serial Murders -- The Nazi Murders -- In the Name of Science -- Hitler$1 (Bs (3z(BScientists(3y (B-- Made in Japan: Unethical Experiments -- Good Old Fashioned American Ingenuity$1 (Band Evil -- Physician Kill Thyself: The Story of Dr. Gwinn E. Puig -- Politics and Medicine -- Libel Plots Against Physicians (Who Killed Dr. Zhivago?) -- Judge, Jury, Executioner, and Doctor -- Trading Treatment for Terror -- Guilty Until Proven Innocent -- What Now? -- Euthanasia, and Assisted Suicide: What Would Hippocrates Do? -- Malpractice or Murder? -- It$1 (Bs All Natural! -- Contagious Caregivers -- Fictitious Physicians: Where Has Marcus Welby Gone? -- Doctors to the Stars.s
Keywords: Medicine; Forensic medicine; Forensic Medicine; Biomedicine; Forensic Science; Forensic Medicine; Popular Science in Medicine and Health